SARS-CoV-2 and animals, a long story that doesn't have to end now: What we need to learn from the emergence of the Omicron variant - Reggiani, Alessandro; Rugna, Gianluca; Bonilauri, Paolo (Frontiers in Veterinary Science, 2022)
OIE, the world organization for animal health, recently released an update on the state of the art of knowledge regarding SARS-CoV-2 in animals. For farmed animals, ferrets and minks were found to be highly susceptible to the virus and develop symptomatic disease both in natural conditions and in experimental infections. Lagomorphs of the species Oryctolagus cuniculus are indicated as highly susceptible to the virus under experimental conditions, but show no symptoms of the disease and do not transmit the virus between conspecifics, unlike raccoon dogs (Nyctereutes procyonoides), which in addition to being highly susceptible to the virus under experimental conditions, can also transmit the virus between conspecifics. Among felines, the circulation of the virus has reached a level of cases such as sometimes suggests the experimental use of vaccines for human use or treatments with monoclonal antibodies. But even among wild animals, several species (White-tailed deer, Egyptian rousettes, and minks) have now been described as potential natural reservoirs of the virus. This proven circulation of SARS-CoV-2 among animals has not been accompanied by the development of an adequate surveillance system that allows following the evolution of the virus among its natural hosts. This will be all the more relevant as the surveillance system in humans inevitably drops and we move to surveillance by sentinels similar to the human flu virus. The lesson that we can draw from the emergence of Omicron and, its more than likely, the animal origin must not be lost, and in this mini-review, we explain why.